MOBILE ASSISTED LANGUAGE LEARNING IMPLEMENTATION IN SELF-EDITING WRITING PROCESS OF STKIP PGRI JOMBANG STUDENTS - Erma Rahayu Lestari; Banu Wicaksono (STKIP PGRI Jombang, 2022)
Self-editing writing process has become very important stage in creating good writing. STKIP PGRI students and lecturers pay more attention to writing content then writing mechanics editing. In this pandemic era teaching and learning activities is limited. This results student needs more assistant in editing their writing. MALL (Mobile Assisted Language Learning) deals with installed applications in mobile phone to support editing writing process This study aims at improving self editing in writing process using application in mobile phones. Grammar and spelling checker applications was used for the purpose of the study. The participants of the study were first semester students of English Department, STKIP PGRI Jombang. In order to achieve the objectives of the study, 2 cycle classroom action research was designed. The study succeeds to apply some self editing techniques as follow: (1) MALL Introduction; which contains installing Proofreader application, observing the application features, observing the example work, (2) Self editing awareness; with some activities of inserting writing work into the application, observing the mistakes, choosing suggested correction, peer editing, (3) Self editing final; which activities are comparing manual self editing and MALL editing work and reconstructing the writing.